Curcumin Extraction, Isolation, Quantification and Its Application in Functional Foods: A Review With a Focus on Immune Enhancement Activities and COVID-19 - Tripathy, Soubhagya; Verma, Deepak Kumar; Thakur, Mamta; Patel, Ami R.; Srivastav, Prem Prakash; Singh, Smita; Gupta, Alok Kumar; Chávez-González, Mónica L.; Aguilar, Cristobal Noe; Chakravorty, Nishant; Verma, Henu Kumar; Utama, Gemilang Lara (Frontiers in Nutrition, 2021)
An entirely unknown species of coronavirus (COVID-19) outbreak occurred in December 2019. COVID-19 has already affected more than 180 million people causing approximately 3.91 million deaths globally till the end of June 2021. During this emergency, the food nutraceuticals can be a potential therapeutic candidate. Curcumin is the natural and safe bioactive compound of the turmeric (Curcuma longa L.) plant and is known to possess potent anti-microbial and immuno-modulatory properties. This review paper covers the various extraction and quantification techniques of curcumin and its usage to produce functional food. The potential of curcumin in boosting the immune system has also been explored. The review will help develop insight and new knowledge about curcumin’s role as an immune-booster and therapeutic agent against COVID-19. The manuscript will also encourage and assist the scientists and researchers who have an association with drug development, pharmacology, functional foods, and nutraceuticals to develop curcumin-based formulations.